RELIGIOUS FUNDAMENTALISM AND VIOLENCE: IS THERE ANY DIRECT CORRELATION BETWEEN FUNDAMENTALISM AND VIOLENCE? - Mujahiduddin, Mujahiduddin (Program Pascasarjana, UIN Alauddin Makassar, 2013)
Tuilsan ini membahas tentang hubungan antara fundamentalisme agama dan kekerasan. Pertanyaan yang ingin diangkat ialah apakah ada hubungan langsung antara fundamentalisme agama dengan kekerasan?. Untuk menjawab pertanyaan ini, maka tulisan ini akan mengemukakan tiga aspek, yaitu, pertama; mendefinisikan istilah fundamentalism dan menjelaskan kerakteristiknya. Kedua, menjelaskan makna dan kategori kekerasan yang digunakan sebagai kerangka teoritis dalam menganalisa hubungan antara fundamentalisme agama dan kekerasan. Ketiga adalah menganalisa hubungan tersebut dan mencoba melihatnya dari perpektif gerakan radikal Islam. Tulisan ini mengasumsikan bahwa kehadiran gerakan fundamentalisme agama tidak selalu punya kaitan dengan kekerasan. Penggunaan kekerasan oleh gerakan fundamentalis sangat tergantung dengan fakto eksternal seperti respon Negara.ABSTRACTThis essay examines the correlation between religious fundamentalism and violent acts. The prominent question addressed in this paper is about is there any direct correlation between fundamentalism and violence?. To answer this inquiry, this writing is going to elaborate three points. First, it defines the term fundamentalism and describes its shared characteristic features. Secondly, it will describe the meaning and categories of violence used in analyzing correlation between religious fundamentalism movements and the utilization of violent actions such as bombing attacks, assassination, kidnapping etc. Thirdly, this article also tries to analyze the links between fundamentalism and violence and how these links are understood in the study of ‘fundamentalist Islam’ and ‘violent political Islam’. This essay argues that the presence of religious fundamentalism such as radical Islamic group does not always connote to violent. Whether or not a religious fundamentalism group will be advocating violent means in its movement is more likely depending on some intermediary factors such as state’s response.